“Det har blivit så vanligt för ungdomarna att dom inte reflekterar över att det är en form av våld” - Livulo,Vanessa; Gunnarsson,Alva (2026)
The digitalisation of adolescents’ everyday lives has created new contexts in which intimate partner violence can occur. Digital intimate partner violence includes controlling, monitoring, and harassing behaviours carried out through digital tools such as social media, messaging applications, and location-sharing services. These behaviours are often normalised among young people, which makes the violence difficult to recognise and address. This study aimed to explore how school counsellors perceive and define digital intimate partner violence among students, how they describe their work with identifying and managing such violence, and which organisational and communicative opportunities and barriers they experience in preventive efforts. The study employed a qualitative research design based on semi-structured interviews with school counsellors working in Swedish upper secondary schools. The empirical material was analysed inductively and interpreted through Eva Lundgren’s theory of the normalisation process and Jürgen Habermas’ theory of communicative action, with particular attention to the concepts of lifeworld and system. The findings show that digital intimate partner violence is often perceived by school counsellors as largely hidden in school settings. According to the counsellors, students rarely describe controlling behaviours as violence, instead framing them as normal or caring aspects of relationships. The results further indicate that this normalisation is not limited to students, as some school counsellors also tend to downplay or overlook such behaviours, particularly when they are described as common or mutual. Consequently, digital intimate partner violence often becomes visible only indirectly through conversations about emotional distress. Dialogue-based counselling was described as a key professional tool for supporting students and challenging the normalisation of unhealthy relationship behaviours.
Keywords: digital intimate partner violence; school counsellors; normalisation; preventive work; students